Heart rate and lactate responses to swimming - Peyrebrune, M. C.; Hardy, C. A. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
The purpose of the study was to determine a relationship between heart rate (HR) and blood lactate (La) levels in swimmers using swimming velocity as the dependent variable. Eleven male competitive swimmers carried out two tests on separate days to establish this relationship. The first test involved a 500 yard incremental swim; lap times were recorded manually, and HR determined from a microcomputer strapped below the chest. The second test involved five successively faster 200 yard repeats with fifteen minuts rest between each. Again lap times were recorded manually, and blood lactate concentrations determined from a finger-prick sample after each stage. Heart rate and La deflection velocities were then identified from graphs obtained in the respective tests. Deflection {d) velocities in the HR test were recorded in eight subjects while no deflection point was observed in the remaining three. Retest results with five of the subjects obtained deflection velocities in two subjects, but none in the three others. Blood lactate deflection velocities were gained in all subjects, and the 2 mM and 4 mM speeds extrapolated from the graphs. Mean (± SD) velocities (m/s) for HR d, La d, 2 mM and 4 mM were 1.334 (± 0.084) mls, 1.257 (± 0.078) mls, 1.291 (± 0.113) m/s and 1.419 (± 0.126) mls respectively. The HR deflection velocity was significantly higher (P < 0.001) than La d velocity and 2 mM velocity, but significantly lower (P < 0.01) than 4 mM/1 velocity. Blood lactate deflection velocity was not significantly different from the 2 mM velocity. The time differences calculated from these speeds for 200 m and 500 m ranged from 4.2 to 18.2 s, and from 10.5 to 45.4 s respectively. The extent of these differences led the researchers to conclude that althouah HR measurements are valuable when more accurate methods are0 not available, there can still be a large margin of error. This index may be unacceptable for the monitoring of training intensity in international class swimmers.